Prospective analysis of 44 consecutive liver transplants performed at a university hospital - Silva,Orlando Castro e (2013)
PURPOSE: To analyze the intraoperative and immediate postoperative biochemical parameters of patients submitted to orthotopic liver transplantation. METHODS: Forty four consecutive orthotopic liver transplants performed from October 2009 to December 2010 were analyzed. The patients (38 male and eight female) were divided into two groups: group A, survivors, and group B, non-survivors. Fifty percent of group A patients were Chid-Pugh C, 40% Chid-Pugh B and 10% Chid-Pugh A. In group B, 52% of the patients were Chid-Pugh C, 41% Chid-Pugh B, and 17% Chid-Pugh A. All orthotopic liver transplants were performed by the piggy-back technique without a portacaval shunt in an anhepatic phase. ALT, AST, LDH and lactate levels were determined preoperatively, at five, 60 minutes after arterial revascularization of the graft and 24 and 48 hours after the end of the surgery.( or: after the surgery was finished). RESULTS: There were no preoperative clinical differences (Child and Meld) between the two groups. The times of warm and hypothermal ischemia were similar for both groups (p>0.05). Serum aminotransferases levels at five and 60 minutes after arterial revascularization of the graft were similar (p>0.05) for both groups, as also were lactate levels at the time points studied. There was no significant difference in Δ lactate between groups at any time point studied (p>0.05). No significant difference was observed between groups during the first 24 and 48 hours after surgery (p>0.05). CONCLUSION: No significant difference in any of the parameters studied was observed between groups. Under the conditions of the present study and considering the parameters evaluated, no direct relationship was detected between the intraoperative situation and the type of evolution of the patients of the two groups studied.